2022
DOI: 10.7717/peerj.14155
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin treatment on post-harvest jujube fruits maintains physicochemical qualities during extended cold storage

Abstract: This study was conducted to investigate the visual appearance and physicochemical changes of postharvest jujube fruits (Ziziphus jujuba Mill. cv. Shucuizao) stored under 0 °C for 15 days. The fruits were dipped in 0 (control), 50, 100, 200 and 400 µM melatonin solutions after harvest. The results showed that treatment with a suitable melatonin concentration improved the rate of crisp fine fruits, delayed weight loss and firmness decline, and suppressed changes in total soluble solids (TSS) and titratable acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Several other researchers have also reported that melatonin administration delayed the decline of TSS during storage ( Miranda et al., 2020 ; Nasser et al., 2022 ). Similarly, administration of melatonin in strawberries ( Liu et al., 2018 ), pitaya ( Ba et al., 2021 ), kiwi fruit ( Wang et al., 2019 ), jujube ( Wang et al., 2022 ), and citrus navel orange ( Ma et al., 2021 ) during postharvest storage resulted in less degradation of TSS and TA. This slow decline in TSS and TA might be attributed to melatonin’s ability to reduce respiration and senescence, thus preserving soluble solids, carbohydrates, and organic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Several other researchers have also reported that melatonin administration delayed the decline of TSS during storage ( Miranda et al., 2020 ; Nasser et al., 2022 ). Similarly, administration of melatonin in strawberries ( Liu et al., 2018 ), pitaya ( Ba et al., 2021 ), kiwi fruit ( Wang et al., 2019 ), jujube ( Wang et al., 2022 ), and citrus navel orange ( Ma et al., 2021 ) during postharvest storage resulted in less degradation of TSS and TA. This slow decline in TSS and TA might be attributed to melatonin’s ability to reduce respiration and senescence, thus preserving soluble solids, carbohydrates, and organic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [16] reported that MT treatment can effectively reduce WL in fruits by enhancing antioxidant activity and controlling reactive oxygen-induced stress. Wang et al [10] tested the different concentrations of MT treatments to control jujube fruit quality, and their findings revealed that increasing the concentration of MT positively enhanced the fruit quality and controlled the WL by limiting the senescence process. This is in accordance with the present study.…”
Section: Index Wl Respiration Rate and Firmnessmentioning
confidence: 99%
“…Among the tested AO enzymes in the pepper fruits, CAT activity was predominant, followed by SOD and POD activity. The prolonged exposure to low temperatures might activate the enzymatic AO system in pepper fruits to respond to physiological stress by increasing the activities of SOD, CAT, and POD [10]. Rodríguez-Ruiz et al [5] reported that CAT activity in pepper fruit is higher than that of SOD and POD due to the modulation of the CAT gene and its activities during the fruit ripening and senescence process.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other researchers have also reported that melatonin administration delayed the decline of TSS during storage (Miranda et al, 2020;Nasser et al, 2022). Similarly, administration of melatonin in strawberries (Liu et al, 2018), pitaya (Ba et al, 2021), kiwi fruit (Wang et al, 2019), jujube (Wang et al, 2022), and citrus navel orange (Ma et al, 2021) during postharvest storage resulted in less degradation of TSS and TA. This slow decline in TSS and TA might be attributed to melatonin's ability to reduce respiration and senescence, thus preserving soluble solids, carbohydrates, and organic acids.…”
Section: Tss Titratable Acidity and Total Sugarmentioning
confidence: 82%